Inhibition of ANXA7 GTPase activity by a small molecule promotes HMBOX1 translation of vascular endothelial cells in vitro and in vivo. (October 2016) - Ma, HanLin; Su, Le; Zhang, ShangLi; Kung, HsiangFu; Miao, JunYing
Abstract: Homeobox containing 1 (HMBOX1) is essential for the survival of human umbilical vein endothelial cells (HUVECs). However, the regulatory mechanism of HMBOX1 expression is still unclear. We recently found that a small molecule 6-amino-2, 3-dihydro-3-hydroxymethyl-1, 4-benzoxazine (ABO) directly targeted annexin A7 (ANXA7) and inhibited its GTPase activity. In addition, both HMBOX1 and ANXA7 participated in the autophagy and apoptosis of HUVECs. But, their relationship in the regulation of HMBOX1 expression is unknown. In this study, we found that ABO could elevate HMBOX1 at translation level through inhibiting ANXA7 GTPase activity. ABO failed to increase HMBOX1 protein level in ANXA7-deficient HUVECs. TGFB2 overlapping transcript 1 ( TGFB2-OT1 ) that was increased by ABO facilitated HMBOX1 expression by increasing La-related protein 1 (LARP1) expression. Furthermore, the protein level of HMBOX1 was decreased under oxidized low-density lipoprotein (oxLDL) treatment in HUVECs and in the aortic endothelium of apolipoprotein E-deficient (apoE −/− ) mice, which could be reversed by ABO in vitro and in vivo. In conclusion, ANXA7 was an endogenous regulator of HMBOX1, and ABO promoted HMBOX1 translation by inhibiting ANXA7 GTPase activity and enhancing TGFB2-OT1 expression. Besides, our data suggested that HMBOX1 might be a novel diagnostic marker and therapeutic target of atherosclerosis.